Recycling oceanic crust for continental crustal growth: Sr–Nd–Hf isotope evidence from granitoids in the western Junggar region, NW China - Tang, G.; Wang, Q.; Wyman, D.; Li, Zheng-Xiang; Xu, Y.; Zhao, Z. (Elsevier BV, 2012)
The juvenile component of accretionary orogenic belts has been declining since the Archean. As a result, there is often controversy regarding the contribution of oceanic basalts to Phanerozoic crustal growth, as in the case of the Central Asian Orogenic Belt (CAOB). Here we report on three groups of Late Carboniferous (316–305 Ma) granitoids in the western Junggar region of northern Xinjiang, NW China, which is part of the southwestern CAOB. They consist of adakites and I and A-type granites, and as a whole have the most depleted isotopic compositions (εNd(t)=+6–+9, (87Sr/86Sr)i=0.7030–0.7045, and εHf(t)=+12–+16) among the granitoids of the CAOB. These features are nearly identical to those of pre-Permian ophiolites in northern Xinjiang, and are clearly different from those of Carboniferous basalts in the western Junggar region. These relationships indicate that the granitoids were mainly derived from recycled oceanic crust by melting of subducted oceanic crust (e.g., adakites), and of the middle–lower crust of intra-oceanic arc that mainly consisted of oceanic crust (e.g., I and A-type granites). Based on evidence from the CAOB, we suggest that recycling of oceanic crust has made a significant contribution to continental crustal growth and evolution during the Phanerozoic.